INFLUENCE OF GENDER AND TERRITORIAL DISTRIBUTION ON SUSCEPTIBILITY TO STEREOTYPE ADVERTISING - L.Spasova (Trakia Journal of Sciences)
The present article aims to investigate the influence of gender and territorial distribution on the susceptibility to stereotypical advertising, looking for some causal relationships between the criteria measuring stereotypical images. The methodology involves the application of three criteria for stereotypical advertising present in the theoretical and empirical studies of Eisend (2019), as well as Akestam, Rosengren, Dahlen, Liljedal and Berg (2021) - trait descriptors, physical characteristics and role behavior. The results of univariate analyzes of variance (ANOVA) show a stronger influence among men compared to women according to the physical characteristics with images of men and women, as well as according to the trait descriptors of men. Female users give more positive advertising responses to role behavior of men, as well as to trait descriptors of women. When measuring the territorial distribution of consumers, divided into two groups: Europe/North America and Turkey/Cyprus show that susceptibility to role behavior in advertising is higher for consumers from Europe and North America, and susceptibility to trait descriptors is higher for consumers from Turkey/Cyprus. Future studies, which should offer a comprehensive theoretical framework, need to focus on some national and cultural characteristics of consumers in stereotype influence, which were not thoroughly studied due to a number of limitations.